A Székely Hadosztály és a Magyar Tanácsköztársaság történetének néhány összefüggése az erdélyi front összeomlásának tükrében - Szilvássy, Zoltán (Hallgatói Műhelytanulmányok, 2022)
Szilvássy, Zoltán: Some connections of the history of Sekler Division and the Hungarian Soviet Republic in the light of the collapse of the Transylvanian Front On April 16, 1919, after a successful attack of Romanian intervention forces the counter-revolutionary Hungarian Székely Division and the Red Army were bot unable to hold the Eastern front line. Unfortunately, and as a result of this event, all the great cities of the Hungarian Plain were fallen, including Debrecen. The red terror, carried out by communists, resulted counter-revolution in Debrecen (18 April, 1919) which was crushed by local communist forces within a short time with the help of Austrian internationalists led by Leo Rothziegel. The loss of the city was especially painful for the Hungarian Soviet Republic because Debrecen was the "capital of the Southeast", a major industrial and agricultural center and an important transport hub. The fate of Debrecen, like the rest of the cities of the Tisza region, was determined by the collapse of the Csucsa front line. In an open field, suffering from lack of munition, the Székely Division could not stop the advance of the Romanian intervention army, which reached the line of the River Tisza. The defense of the historic area of the Kingdom of Hungary was not included in the aims of the Hungarian Soviet Republic, which used Hungary as a springboard in the process of spreading the world revolution. The betrayal of the effort for the territorial integrity of the country caused a huge gap between the Székely Division and the communist forces which resulted the collapse of the Transylvanian Front line.